Herod Antipas in Galilee: the literary and archaeological sources on the reign of Herod Antipas and its socio-economic impact on Galilee - Jensen, Morten Hørning (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2010)
The quest for the secrets of first-century Galilee has become an issue of intense interest in recent research. In particular, a growing interest can be traced in Herod Antipas' impact on the region's socio-economic stability. Was he good or bad news for the ordinary rural peasant population, and did his urbanization programme have a crucial impact on the Historical Jesus? Morten Hørning Jensen seeks to survey the literary and archaeological sources on the reign of Antipas with a view to determining its socio-economic impact on the region. He argues that Antipas' impact on early first-century Galilee was probably more moderate than Historical Jesus scholars have generally assumed until now.